Effects of cytoplasm on heterosis for agronomic traits in upland cotton (Gossypium hirsutum ) - TUTEJA, O P; BANGA, MANJU (The Indian Journal of Agricultural Sciences, 2011)
The effects of cytoplasm on productivity and heterosis for seed cotton (Gossypium hirsutum L.) yield and its component was studied in 64 hybrids . Four male sterile (A) lines CMS F 505, CMS CSH 2379, CMS LRA 5166 and CMS Jhorar and their corresponding maintainer (B) lines were crossed with eight restorer lines in a line Ã— tester design. The 64 crosses and a standard check, CSHH 198, were grown in a randomized block design with three replications during 2008â€“09. Analysis of variance revealed significant differences among genotypes. Cytoplasmic effects were estimated by comparing A Ã— R and B Ã— R hybrids combinations. Both positive and negative cytoplasmic effects were observed for all the characters studied. On the basis of mean of two groups of hybrids, it was revealed that cytoplasm significantly decreased number of bolls/plant, 2.5% span length, maturity coefficient, micronaire value and fibre strength as compared to normal cytoplasm. The estimation of standard heterosis of individual crosses showed that Gossypium G. harknessii cytoplasm imparting sterility also influenced heterosis in most of the crosses. Among CMS-based hybrids, CMS Jhorar Ã— CIR 920 Pâ‚â»â‚ƒ (1 574 kg/ha), and among conventional hybrids F 505 Ã— CIR 526 Pâ‚‚ (1 944 kg/ha) were found to be highest yielding. The range of heterosis varied from â€“8.8 to 29.9 % in conventional hybrids while heterosis range of CMS cross combinations varied from â€“5.2 to 5.2 % for seed cotton yield. The combination, CMS F 505 Ã— CIR 126 Pâ‚‚â»â‚ recorded the highest number of bolls (60.9), and was heterotic by a magnitude of 25.0%, while the highest heterotic effect was observed in F 505 Ã— CIR 97 Pâ‚ƒâ»â‚„ (37.9%) in conventional crosses. Similar effect of G. harknessii cytoplasm has been observed for other characters studied. It is thus the interaction of particular cytoplasm with the nuclear genes that affects performance. It would be more appropriate to test the CMS lines in different combinations rather than converting the female parent of released hybrids into male sterile lines.